A Life Cycle Assessment on the Dehairing of Rawhides: Chemical Treatment versus Enzymatic Recovery through Solid State Fermentation. (16th April 2018) - Catalán, Eva; Komilis, Dimitrios; Sánchez, Antoni
Summary: The leather industry needs to switch from the traditional chemically based dehairing process to an environmentally friendly one so that the overall burdens to the environment are reduced. The primary goal of the work was thus to compare the chemical leather dehairing process to an enzymatically based one using the enzymes that are extracted after the application of solid state fermentation (SSF) on hair wastes generated after dehairing. The environmental burdens of the dehairing stage were determined using a life cycle assessment (LCA) approach by comparing the two aforementioned management scenarios. The first scenario was the commonly used technology in which hair is removed via a chemical process and then composted in open piles. This scenario included two subscenarios where hair waste is either incinerated or landfilled. In the second scenario, the proteolytic enzymes extracted during the SSF of the residual hair are used to dehair the new rawhides instead of chemicals. Industrial and laboratory data were combined with international databases using the SimaPro 8.0 LCA software to make comparisons. The environmental impacts associated with the enzymatic dehairing were significantly lower than the ones associated to the conventional chemical dehairing process. This difference is attributed to the impacts associated with the original production of the chemicals and to the electricity consumed in the conventional method. A sensitivity analysis revealed that the results are affected by the amounts of chemicals used during dehairing.